ANALISIS NERACA AIR UNTUK TANAMAN PADI DALAM UPAYA ADAPTASI DANMITIGASI BENCANA TERHADAP KELOMPOK RENTAN - Henny Puspita Sari; Suci Kurnia Sari (Ekasakti Jurnal Penelitian dan Pengabdian, 2023)
Although climate change is of concern to hydrologists, climatologists, environmentalists, agronomists, it is predicted that it will have serious impacts on water resources, infrastructure, agriculture, biological and ecosystem functions, and human health. Serious problems arise in some areas due to fluctuations in water supply, especially during the rainy and dry seasons. Water balance (water balance) that cannot be accommodated, is calculated by analyzing rainfall, temperature, humidity, sunlight, wind speed and evapotranspiration. Better rice yields, achieved by preventing or overcoming disasters in an area. This research was conducted in May-August 2022, using secondary data, namely: collection of climate data and production data, vulnerability maps in Padang Pariaman Regency, which were then analyzed using the Penman Monteith method. Padang Pariaman Regency in 2021 experienced a water deficit period in February. This is probably caused by the large evapotranspiration in the region. However, the estimated ETP values obtained were quite high, namely an average of 5.22 mm/day and 161.15 mm/month. Based on the results of the analysis of rice farming in Padang Pariaman Regency, the R/C ratio is 2.02> 1. However, the reality on the ground is not like that. So that farmers carry out land conversion on the commodity corn fodder.